2000
DOI: 10.1039/a910232i
|View full text |Cite
|
Sign up to set email alerts
|

The dinuclear manganese complex Mn2O(OAc)2(TPTN) as a catalyst for epoxidations with hydrogen peroxide

Abstract: The dinuclear manganese complex Mn2O(OAc)(2)(TPTN) as a catalyst for epoxidations with hydrogen peroxide Brinksma, J.; Hage, R.; Kerschner, J.; Feringa, B.L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…with respect to the substrate) to a mixture of alkene, the Mn-tmtacn catalyst (0.1 mol%), and gmha (25 mol%) in CH 3 CN at 0 C. Under these reaction conditions high conversions are reached, whereas only 30% excess of oxidant with respect to substrate was required (Table 11.8). The H 2 O 2 efficiency represented a dramatic improvement compared to previous Mn-based systems [132]. In most cases the conversions were also significantly higher than those obtained with oxalate as co-catalyst using 1.3 equiv.…”
Section: Triazacyclononane Derivativesmentioning
confidence: 55%
See 1 more Smart Citation
“…with respect to the substrate) to a mixture of alkene, the Mn-tmtacn catalyst (0.1 mol%), and gmha (25 mol%) in CH 3 CN at 0 C. Under these reaction conditions high conversions are reached, whereas only 30% excess of oxidant with respect to substrate was required (Table 11.8). The H 2 O 2 efficiency represented a dramatic improvement compared to previous Mn-based systems [132]. In most cases the conversions were also significantly higher than those obtained with oxalate as co-catalyst using 1.3 equiv.…”
Section: Triazacyclononane Derivativesmentioning
confidence: 55%
“…High epoxidation activity was found for manganese complexes based on dinucleating ligand N,N,N 0 ,N 00 -tetrakis(2-pyridylmethyl)-1,3-propanediamine (tptn) [132]. The ligand contains a three-carbon spacer between the three-N-donor sets.…”
Section: Manganese Complexes For Alkene Oxidation Based On Pyridyl LImentioning
confidence: 99%
“…In this respect, pyridylamine ligands represent an interesting alternative. Feringa and coworkers found that the dinuclear manganese complex 14, prepared from the tetra-pyridyl ligand 13, was an efficient catalyst for the epoxidation of simple olefins [67]. Only 0.1 mol % of catalyst 14 was required for high levels of conversion (87 %) of cyclohexene into its corresponding epoxide.…”
Section: Scheme 66mentioning
confidence: 99%
“…1,2 Recently, hexadentate ligands that contain two terminal tridentate coordination sites connected by flexible linkers are often used for this purpose to prepare such complexes. 3,4 N,N,N′,N′-Tetrakis(2-pyridylmethyl)-1,6-hexanediamine is one of representative ligands that have two terminal tridentate NNN-coordination sites connected by a hexamethylene linker. 5 While attempting to prepare a new μ-hydroxo-bis-μ-carboxylato triply bridged dicopper(II) complex with tphn, we obtained single crystals of a new complex [Cu2(OAc)2(BF4)(tphn)(H2O)]BF4·CH2Cl2 (1).…”
mentioning
confidence: 99%
“…1,2 Recently, hexadentate ligands that contain two terminal tridentate coordination sites connected by flexible linkers are often used for this purpose to prepare such complexes. 3,4 N, N,N′, X-Ray difraction measurements were made on a Rigaku VariMax Saturn CCD 724+ diffractometer with graphite monochromated Mo Kα radiation at 113 K. The structure was solved by direct methods (SIR92) and expanded using Fourier techniques. The non-hydrogen atoms were refined anisotropically.…”
mentioning
confidence: 99%